HUBUNGAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENERIMA LAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TANAH DATAR - Mita Wulandari; Armida S (Jurnal Ecogen, 2019)
This study aims to determine the relationship of service quality to the satisfaction of recipients of population administration services at the Population and Civil Registry Office of Tanah Datar District. Measurement of service quality dimensions using five dimensions of service quality consisting of dimensions of physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy). This type of research is a quantitative study with a correlational method using SPSS version 22. The population of this study is the population receiving population administration services in Dukcapil Tanah Datar District, a population of 82,286 people with a sample of 100 people taken using the Slovin formula using accidental sampling techniques. The research data is primary data, the data collection technique in this study is to use a questionnaire prepared using a Likert scale whose scores are 1-5. To ensure that the instruments used in the study are validity and reliability tests. Data were analyzed by descriptive and inductive analysis using normality test, linearity test, hypothesis testing using multiple correlation test, person correlation test, and the coefficient of determination test with α = 0.05. The results of this study show that the five service quality variables have a positive and significant relationship to the satisfaction of recipients of population administration services, namely the dimensions of physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy). Keyword:  kualitas pelayanan, bukti fisik (tangibility), keandalan (reliability), daya tanggap (responsiveness), jaminan (assurance), empati (emphaty), dan kepuasan masyarakat penerima layanan.